Meningkatkan Aktivitas Belajar Siswa Menggunakan Metode Kerja Kelompok Pada Pembelajaran Ilmu Pengetahuan Alam Kelas IV SDN 1 Pokoh Kidul - Devi Ratana Purnamasari (STABN RADEN WIJAYA WONOGIRI JAWA TENGAH, 2021)
This study aims to develop flashcard material for reading at the beginning of the first grade of elementary school. To achieve this goal, this study uses qualitative research methods. Based on the results of the small group test, the following data were obtained: (1) 100% Enjoyment, (2) 100% Security, (3) 100% Comfort, (4) 96.87% Language Aspect. Based on large group testing, the following data were obtained: (1) Enjoyment 94D44 (2) Security 100% (3) Comfort 94% (4) Language Aspect 97.18%. Based on the data obtained above, this multimedia flashcard product can be used without modification as an alternative to Indonesian learning to train the initial reading skills of grade 1 students of SDN 1 Pokoh Kidul